Manuscripts of Antoni HabeVs symphonies in Wielkopolska archives - Gołębiowska, Julia (Interdisciplinary Studies in Musicology, 2018)
The main aim of this article is to present the manuscripts of Antoni Habel’s symphonies preserved in archives in the Wielkopolska region of Poland and attempt to order them chronologically in respect to their dates of composition. Habel lived in Gniezno around the turn of the nineteenth century. Most of our information about him comes from payroll registers, inventories and other documents preserved in the Archiépiscopal Archive of Gniezno, but they do not contain any information about his symphonies. The following works by Habel have survived to this day: a Sinfonia D, preserved in two copies (in Grodzisk and Gniezno), and a Sinfonia ex F, preserved in Gostyń. A critical analysis of these two compositions allows us to indicate which was composed first, since the simplicity of the composition techniques used in the F major Symphony suggests that it is older than the D major. We must also address, however, the question of the differences between the two copies of the D major Symphony, which vary with regard to melody, rhythm, dynamics, articulation and even form. Analysis makes it possible to reconstruct the order in which the two manuscripts were produced and determine the original version of the D major Symphony.